The Design Of Resort Hotel In TukTuk (Neo-Vernacular Architecture) - Melinda , Elvina; Rahman , N. Vinky (Talenta Publisher, 2019)
Tuktuk Siadong located on Samosir Island has amazing natural potential and cultural characteristics that make Tuktuk one of the favorite destinations of tourists. To fulfill the growth and needs of tourists in Tuktuk anaccommodation in the form of a Resort Hotel is needed. This design begins with a literature study and is followed by a field survey to produce the data needed ina design concept. These concepts produced a Resort Hotel design themed Neo-Vernacular Architecture that developed the basic principles of Batak Toba architecture and applied them in design. Resort hotels that are designed to be lodging accommodations that have supporting facilities to serve tourists who come.